Effects of transtheoretical model (TTM) stage-based intervention on TTM variables among Iranian sedentary high school students - Ghiami, Zeinab (2014)
This study aimed to evaluate the effect of a stage-based intervention on psychological variables among Iranian sedentary high school students. Another objective of the study was to examine relationships of TTM variables (processes of change, decisional balance and self-efficacy) with stages of change (action stage) to identify determinants of improving physical activity. Participants in this study were Iranian sedentary high school students (N=56) who were randomly assigned as an experimental group (n = 28) and a control group (n= 28). A pretest- posttest design was used in the present study. The experimental group received a 16-week TTM stage-based intervention, while the control group attended regular physical education course. The intervention developed in this study consisted of a flexible series of strategies that aimed to help those in the sedentary category live an active life by influencing their attitudes towards physical activity. After the completion of the intervention, four tests were administered to all participants to measure their processes of change, decisional balance, self-efficacy, and stages of change. The participants’ pre-test, post-test 1, and post-test 2 scores in all tests were analyzed to determine the effectiveness of the TTM stage-based intervention on the experimental group’s TTM variables. The results of repeated measures ANOVA showed a statistically significant difference between the mean test scores of processes of change, decisional balance, and self-efficacy in the pre-, post-test 1, and post-test 2 measurements in the experimental group, F (2, 54) = 163.863, p < .05; F (2, 54) = 152.404, p < .05; and F (2, 54) = 151.359, p < .05, respectively. Further, the independent samples t-test analysis of the post-test 2 scores of the experimental and control groups revealed that the difference between the mean scores of the two groups was significant in processes of change (t = 20.46, df = 39 and p < .05),decisional balance (t = 24, df = 53 and p < .05), and self-efficacy (t = 20, df = 52 and p < .05). Thus, the findings of the study provided evidence that stage-based intervention had a significant effect on TTM variables, which have been shown to enhance sedentary students’ psychological factors and also their stages of change regarding physical activity behaviour.